Análise da eficiência de contratos de serviços de elevada especificidade terceirizados pela petrobras - Costa, Antonio Rufino da (2013)
The definition of the boundaries of the firms is subject that has occupied the organizational theorists long ago, being the seminal work of Coase (1937) indicated as the trigger for one theoretical evolution, with emphasis on governance structures, which led to a modern theory of incomplete contracts. The Transaction Cost Economics (TCE) and Agency Theory arise within this evolution, being widely used in studies related to the theme. Empirically, data envelopment analysis (DEA) has established itself as a suitable tool for analysis of efficiency. Although TCE argues that specific assets must be internalized, recent studies outside the mainstream of theory show that, often, firms may decide, for various reasons, hire them on the market. Researches on transaction costs face with the unavailability of information and methodological difficulties in measuring their critical variables. There`s still the need for further methodological deepening. The theoretical framework includes classic works of TCE and Agency Theory, but also more recent works, outside the mainstream of TCE, which warn about the existence of strategies in use of specific assets that aren`t necessarily aligned with the classical ideas of TCE. The Brazilian oil industry is the focus of this thesis, that aimed to evaluate the efficiency of contracts involving high specificity service outsourced by Petrobras. In order to this, we made the categorization of outsourced services in terms of specificity, as well the description of services with higher specificity. Then, we verified the existence of relationship between the specificity of services and a number of variables, being found divergent results than those that are preached by the mainstream of TCE. Then, we designed a DEA model to analyze the efficiency in the use of onshore drilling rigs, identified among the services of highest specificity. The next step was the application of the model to evaluate the performance of drilling rigs contracts. Finally, we verified the existence of relationship between the efficiency of contracts and a number of variables, being found, again, results not consistent with the theory mainstream. Regarding to analyze of efficiency of drilling rigs contracts, the model developed is compatible with what is found in academic productions in efficiency of drilling rigs. The results on efficiency show a wide range of scores, with efficiencies ranging from 31.79% to 100%, being low the sample efficiency average. There is consonance between the model results and the practices adopted by Petrobras. The results strengthen the DEA as an important tool in studies of efficiency with possibility to use for analysis other types of contracts. In terms of theoretical findings, the results reinforce the arguments that there are situations in which the strategies of the organizations, in terms of use of assets and services of high specificity, do not necessarily follow what is recommended by the mainstream of TCE